EFL Teacher Perceptions of Error Correction in Grammar Teaching: A Case Study - Iftikhar, Ahmad; Noor Raha, Mohd Radzuan (Universiti Malaysia Pahang, 2015)
This study investigated non-native English as a Foreign Language (EFL) teachers’ perceptions regarding error correction in grammar teaching in Qassim University, Saudi Arabia. The main data collection tool of this study was a five-point Likert-scale questionnaire, administered to 48 EFL teachers. In order to triangulate the study, four semi-structured interviews were conducted. Participants were selected based on convenience sampling. The study attempted to identify experience-based and gender-based differences among EFL teachers about error correction in grammar teaching. Descriptive analyses and independent-samples t-tests were run using a statistical software, SPSS. The results show that there were no differences of perceptions across teaching experience and across genders.The findings of the study revealed that experienced and less experienced and male and female teachers’ perceptions about error correction in grammar teaching are independent of these individual characteristics. Eventually, implications of this study are identified for effective teaching of error correction in grammar.